Characterization of Antibiotic Resistance in Select Tertiary Hospitals in Uganda: An Evaluation of 2020 to 2023 Routine Surveillance Data - Mayito, Jonathan; Kibombo, Daniel; Olaro, Charles; Nabadda, Susan; Guma, Consolata; Nabukenya, Immaculate; Busuge, Andrew; Dhikusooka, Flavia; Andema, Alex; Mukobi, Peter; Onyachi, Nathan; Watmon, Ben; et al. (Tropical Medicine and Infectious Disease, 2024)
Antimicrobial resistance (AMR) is a public health concern in Uganda. We sought to conduct an extended profiling of AMR burden at selected Ugandan tertiary hospitals. We analyzed routine surveillance data collected between October 2020 and March 2023 from 10 tertiary hospitals. The analysis was stratified according to the hospital unit, age, gender, specimen type, and time. Up to 2754 isolates were recovered, primarily from pus: 1443 (52.4%); urine: 1035 (37.6%); and blood: 245 (8.9%). Most pathogens were Staphylococcus aureus, 1020 (37%), Escherichia coli, 808 (29.3%), and Klebsiella spp., 200 (7.3%). Only 28% of Escherichia coli and 42% of the other Enterobacterales were susceptible to ceftriaxone, while only 44% of Staphylococcus aureus were susceptible to methicillin (56% were MRSA). Enterococcus spp. susceptibility to vancomycin was 72%. The 5–24-year-old had 8% lower ampicillin susceptibility than the >65-year-old, while the 25–44-year-old had 8% lower ciprofloxacin susceptibility than the >65-year-old. The 0–4-year-old had 8% higher ciprofloxacin susceptibility. Only erythromycin susceptibility varied by sex, being higher in males. Escherichia coli ciprofloxacin susceptibility in blood (57%) was higher than in urine (39%) or pus (28%), as was ceftriaxone susceptibility in blood (44%) versusurine (34%)orpus(14%). Klebsiellaspp. susceptibility to ciprofloxacin and meropenem decreased by 55% and 47%, respectively, during the evaluation period. During the same period, Escherichia coli ciprofloxacin susceptibility decreased by 40%, while Staphylococcus aureus gentamicin susceptibility decreased by 37%. Resistance was high across the Access and Watch antibiotic categories, varying with time, age, sex, specimen type, and hospital unit. Effective antimicrobial stewardship targeted at the critical AMR drivers is urgently needed.
Keywords: Antimicrobial resistance; AMR; Antibiotic resistance; Bacterial antimicrobial resistance; AMR surveillance